Hemp inflorescence meal as a novel feed ingredient in laying hens: Safety assessment, nutritional characterization, and effects on egg quality - Hathairat Saengsuwan; Chaiyapoom Bunchasak; Choawit Rakangthong; Kanokporn Poungpong (Veterinary World)
Background and Aim: Hemp inflorescence meal (HIM) is a byproduct of cannabinoid extraction and offers a sustainable, nutrient-rich alternative for animal feed. However, its application in poultry diets remains limited due to concerns regarding residual cannabinoid transfer to eggs. This study aimed to evaluate the nutritional composition, metabolizable energy, production performance, egg quality, and cannabinoid residue safety of HIM when included in laying hen diets.